Prospects and challenges for the export of rare earths from Sub-Saharan Africa to the EU - Dirk Kohnert (Zenodo, 2024)
The African continent is increasingly becoming a battleground in the race between superpowers for access to critical minerals needed for the 'Green Revolution', such as rare earth minerals (REE). Companies from China, the USA and Russia play a major role. In most cases, critical minerals are mined by international mining companies supported by their governments and organizing complex global value chains. So far, China has dominated supply chains and has secured mining contracts across sub-Saharan Africa (SSA). Currently, China produces 58% of all REEs worldwide. It is the main importer of minerals from Africa, with mineral exports from sub-Saharan Africa to China totalling USD 10 bn in 2019. Its dominance of the global rare earths market is rooted in politics, not geography. Rare earths are neither that rare nor that concentrated in China. Beijing has adopted a strategy of imports, dumping and control of rare earths that is hardly consistent with WTO rules. Therefore, in June 2022, a newly founded 'Minerals Security Partnership', consisting of the USA, the EU, Great Britain and other Western industrialized countries, invited mineral-rich African countries to counter Chinese dominance. These included resource-rich countries such as South Africa, Botswana, Angola, Mozambique, Namibia, Tanzania, Zambia, Uganda and the Democratic Republic of Congo. The West's push became even more urgent after Beijing imposed export controls on the strategic metals gallium and germanium in July 2023, sparking global fears that China could be next to block exports of rare earth or processing technology. Because African markets are small, they are forced to rely on foreign financing. However, so far, foreign direct investment in rare earth production has confirmed the 'pollution haven' hypothesis about the environmentally harmful effects of FDI flowing into the affected countries. Although the full potential of rare earths in SSA has remained largely untapped due to low exploration, the dark side of the energy transition is becoming increasingly visible. These include pollution of soil, air and water as well as inadequate disposal of toxic residues and intensive water and energy use, occupational and environmental risks, child labour and sexual abuse as well as corruption and armed conflicts. In August 2023, Nigeria, Africa's largest economy, suspended certain illegal Chinese mining activities within its borders, including the activities of Ruitai Mining Company due to its involvement in illegal titanium ore mining. Namibia and the DR Congo followed suit. – – Der afrikanische Kontinent wird immer mehr zum Schlachtfeld im Wettlauf zwischen Supermächten um den Zugang zu kritischen Mineralien, die für die ,Grüne Revolution` benötigt werden, wie zum Beispiel seltene Erden (REE). Eine große Rolle spielen Unternehmen aus China, den USA und Russland. In den meisten Fällen werden kritische Mineralien von internationalen Bergbauunternehmen abgebaut, die von ihren Regierungen unterstützt werden und komplexe globale Wertschöpfungsketten organisieren. Bisher dominiert China die Lieferketten und hat sich Bergbauverträge in ganz Afrika südlich der Sahara (SSA) gesichert. Derzeit produziert China 58 % aller REEs weltweit. Es ist der Hauptimporteur von Mineralien aus Afrika, wobei sich die Mineralienexporte aus Afrika südlich der Sahara nach China im Jahr 2019 auf insgesamt USD 10 Mrd. beliefen. Seine Dominanz auf dem globalen Markt für seltene Erden hat seine Wurzeln in der Politik, nicht in der Geographie. Seltene Erden sind weder so selten noch so stark in China konzentriert. Peking hat eine Strategie der Einfuhr, Dumpings und Kontrolle seltener Erden eingeführt, die kaum mit den Regeln der WTO übereinstimmt. Daher lud im Juni 2022 eine neu gegründete ,Minerals Security Partnership`, bestehend aus den USA, der EU, Großbritannien und anderen westlichen Industrieländern, mineralreiche Länder Afrikas ein, der chinesischen Dominanz entgegenzuwirken. Dazu gehörten rohstoffreiche Länder wie Südafrika, Botswana, Angola, Mosambik, Namibia, Tansania, Sambia, Uganda und die Demokratische Republik Kongo. Der Vorstoß des Westens wurde noch dringlicher, nachdem Peking im Juli 2023 Exportkontrollen für die strategischen Metalle Gallium und Germanium eingeführt hatte, was weltweit Befürchtungen weckte, dass China als nächstes den Export von Seltenen Erden oder Verarbeitungstechnologie blockieren könnte. Da die afrikanischen Märkte klein sind, sind sie gezwungen, auf ausländische Finanzmittel zurückzugreifen. Bisher haben die ausländischen Direktinvestitionen in die Produktion von Seltenen Erden jedoch die ,Pollution haven` Hypothese über die umweltschädlichen Auswirkungen der in die betroffenen Länder fließenden FDI bestätigt. Obwohl das volle Potenzial der seltenen Erden in SSA aufgrund der geringen Exploration bisher weitgehend ungenutzt blieb, werden die Schattenseiten der Energiewende zunehmend sichtbar. Darunter fallen die Verschmutzung von Boden, Luft und Wasser sowie die unzureichende Entsorgung giftiger Rückstände und die intensive Wasser- und Energienutzung, Arbeits- und Umweltrisiken, Kinderarbeit und sexueller Missbrauch sowie Korruption und bewaffnete Konflikte. Im August 2023 stellte Nigeria, Afrikas größte Volkswirtschaft, bestimmte illegale chinesische Bergbauaktivitäten innerhalb seiner Grenzen ein, einschließlich der Aktivitäten der Ruitai Mining Company wegen ihrer Beteiligung am illegalen Titanerzabbau. Namibia und die DR Kongo folgten diesem Beispiel.
Keywords: D24; D43; D52; E23; F13; F18; F63; L61; N54; Q53; 330; rare earths; energy transition; climate change; pollution; emerging markets; Sub-Saharan Africa